ANALISIS ICOR TERHADAP KEBUTUHAN INVESTASI SEKTOR PERDAGANGAN, HOTEL, DAN RESTORAN DI PROVINSI NUSA TENGGARA BARAT - Didi Suwardi; Fitria Permata Cita; Rozzy Aprirachman (Jurnal Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the investment requirements in the trade, hotel, and restaurant sector to support economic growth in the Province of West Nusa Tenggara (NTB) during 2009–2013. The trade, hotel, and restaurant sector is considered one of the strategic sectors contributing significantly to the Gross Regional Domestic Product (GRDP) of NTB Province and playing an important role in employment absorption and regional economic development. Therefore, appropriate investment planning is required to support regional economic growth targets. This research employs a descriptive research design with a quantitative approach. The data used are secondary data consisting of GRDP data of the trade, hotel, and restaurant sector, economic growth rates, and investment data of Domestic Investment (PMDN) and Foreign Investment (PMA) in NTB Province from 2004 to 2008. The analytical method used in this study is the Incremental Capital Output Ratio (ICOR) method to calculate the investment requirements needed to achieve the economic growth targets in the trade, hotel, and restaurant sector during 2009–2013. The results indicate that the trade, hotel, and restaurant sector plays an important role in the formation of the GRDP of NTB Province. The ICOR value obtained shows that investment requirements in this sector continue to increase along with the economic growth targets established by the regional government. Therefore, effective and efficient investment enhancement is highly needed to support regional economic growth and improve public welfare.